ANALISIS RESPONS SISWA TERHADAP MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN PENDEKATAN CONCRETE REPRESENTATIONAL ABSTRACT (CRA) - Kusuma, Dinda Tria; Susiyawati , Enny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the response of students to discovery learning model through concrete representational abstract (CRA) approach in science learning at junior high school. This study use a quasi experimental method with a Likert scale for each statement involving 28 students in class VIII C of MTsN 2 Sidoarjo. The result of study were obtained from questionnaire sheet of student responses in learning consisting of 14 statement and analyzed using descriptive statistic. The results showed that the discovery learning model with the CRA approach received positive responses from students, with an average score of 77%, which was categorised as ‘Good’ for the learning process using the discovery learning model with the CRA approach. This indicates that the learning process was well received and that students found it easier to understand the material and maximise the learning objectives.